Inefficient continuation decisions, job creation costs, and the cost of business cycles - Den Haan, W; Sedlacek, P (Wiley, 2014)
This paper develops a model according to which the costs of business cycles are nontrivial because they reduce the average level of output. The reason is an interaction between job creation costs and an agency problem. The agency problem triggers separations during economic downturns even though both the employer and the worker would be better off if the job was not discontinued, that is, affected jobs have strictly positive surplus values. Similarly, booms make it possible for more jobs to overcome the agency problem. These effects do not offset each other, because business cycles reduce the expected job duration for these jobs. With positive job creation costs, business cycles then reduce the creation of valuable jobs and lower average activity levels. Considering a wide range of parameter values, we find estimates for the cost of business cycles ranging from 2.03% to 12.7% of gross domestic product.